Tendencies in medical negligence, with special reference to Hungary - Julesz, Máté J (Zbornik radova Pravnog fakulteta u Novom Sadu, 2020)
Medical negligence has long been in the focus of legal research in most countries. In some countries, the negligence standard has been replaced by the avoidability standard, the latter leading to a no-fault system. Nonetheless, most legal systems apply the negligence standard. In my opinion, the negligence standard should be sustained because, despite the undoubted advantages of the no-fault system, the ’good old law’ on medical negligence promotes greater legal certainty and patient safety. Criminal medical negligence differs from civil medical negligence as regards onus, as well as in other ways. In the UK, many lawyers and physicians have protested against the legal practice of gross negligence manslaughter, an effort which may also serve as an example for other countries. In most continental European countries, the enforcement of a foreign punitive damages judgment would run counter to the ordre public; however, in some countries, such as in France and Hungary, a punitive damages judgment might be enforced.